KEDUDUKAN HUKUM SURAT KETERANGAN TANAH DALAM SISTEM PEMBUKTIAN PENGUASAAN HAK ATAS TANAH - Anri, Andi Fini Rathi; Heryanti, Heryanti; Ukkas, Jumiati; Intan, Nur; Safiuddin, Sahrina (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2024)
The aim of this study is to examine the legal position of the Land Certificate Letter (SKT) within the land rights proof system and to assess its evidentiary strength. The research method employed is a descriptive qualitative approach with a normative framework, as it is deemed most suitable for analyzing the legal status of SKT in relation to land rights proof under applicable regulations. SKT is commonly used as preliminary evidence of physical possession of land. However, within the evidentiary system, it holds weaker legal weight compared to a land certificate issued by the National Land Agency (BPN). While SKT may be accepted as evidence in court during land disputes, it does not provide the same level of legal certainty as a land certificate. A land certificate serves as a more robust and legitimate proof of ownership, offering greater legal protection. SKT functions solely as an initial proof and basis for land registration. Consequently, despite its significant role in administrative procedures, SKT does not offer absolute legal protection and may be contested by parties holding stronger evidence of ownership. This study also underscores the importance of raising public awareness regarding the differences in legal strength between SKT and land certificates to ensure better understanding of the significance of land registration for legal certainty.